2014
DOI: 10.22437/ppd.v1i4.1715
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Nilai Tambah Keripik Ubi Kayu di UKM Barokah Kabupaten Bone Bolango

Abstract: This study aims to determine the Value Added Analysis of Cassava Chips in SME "Chips Barokah" Bonebolango District . This study was carried on in the village Lamahu District of Southern District Bonebolango Bulango performed on the month from October to December in 2013 . The method of analysis used in this study is the case study method is the method of data collection in a comprehensive manner , the determination of where the research is done on purpose , as for the type of data used is primary data and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Gethuk profit is IDR 69,275,800.00 and Balung Kethek is IDR 3,256,035.00. Imran, Murtisari, & Murni's (2014) research showed that processing cassava into chips generates profit of IDR 6,116,500.00. The profit of Gethuk is greater than the chips.…”
Section: Results and Discussion Profit Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Gethuk profit is IDR 69,275,800.00 and Balung Kethek is IDR 3,256,035.00. Imran, Murtisari, & Murni's (2014) research showed that processing cassava into chips generates profit of IDR 6,116,500.00. The profit of Gethuk is greater than the chips.…”
Section: Results and Discussion Profit Analysismentioning
confidence: 99%
“…This is because the B / C ratio value of Gethuk is efficient and Balung Kethek contributes to the profits seen from the R / C ratio value of more than 1 (Hariance et al, 2018). Imran, Murtisari, & Murni's (2014) research on added value analysis of cassava chips in Bone Bolango Regency showed that cassava processing is efficient with an R / C ratio of 2.20. Research by Ishak et al (2017) showed that the B / C ratio for processing cassava into chips was 2.5.…”
Section: Business Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…Penanganan pasca panen dengan mengolah ubi kayu menjadi tepung mocaf, tape, getuk, tiwul yang merupakan hasil dari nilai tambah produk. Hal ini di dukung oleh Imran et al (2014) yang menyatakan bahwa peningkatan nilai tambah produk dengan cara pengawetan produk pertanian menjadi produk olahan yang lebih tahan lama atau siap dikonsumsi pada komoditas ubi kayu sangat diperlukan.…”
Section: Inovator (Variabel X2)unclassified
“…Perhitungan nilai tambah yang dilakukan pada proses pengolahan nira dengan tujuan untuk mengukur besarnya nilai tambah yang terjadi akibat adanya proses pengolahan nira menjadi gula aren yang siap dipasarkan. Penelitian mengenai nilai tambah yang menggunakan perhitungan metode Hayami telah banyak dilakukan pada penilaian nilai tambah komoditas pertanian menjadi produk jadi seperti dilakukan oleh (Putra et al, 2020), (Nuzuliyah, 2018) dan (MARYANI et al, 2018). Hasil analisis nilai tambah produk gula aren secara rinci pada tabel berikut 6) 11a)=( 10)-( 8)-( 9) 11b)=(11a/10)x100 12a)=( 5)x( 7 Tabel diatas menunjukkan perhitungan nilai tambah produksi gula aren.…”
Section: Metode Penelitianunclassified